PERAN UNICEF TERHADAP PERDAGANGAN ANAK DI VIETNAM (2008-2011) - Avisenna, Richardo; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains about how the UNICEF’s roles as international organization in overcoming child trafficking in Vietnam (2008-2011). Child trafficking is the one of international politic issues who forbids Human Rights especially for children. Vietnam is country which has high level in child trafficking activity. UNICEF as international organization was established on September, 11th 1946 and has headquarters in New York, has roles for being advocacy to children’s rights. Besides UNICEF also has obligation to fulfill goals of MDG’s program in 2015, is all societies in the world should get their rights in this case especially for children.This research used qualitative methods. In this research, the data was collected by using library research technique where this technique is collecting data sources from the literature, like books, website official publications, newspaper, and journal.This research uses pluralism approach which this approach has assumption that actor in international relation isn’t just a state but there’s another actor one of International organization. In this research, writer uses International Organization Theory which each organization has their duty. This research of UNICEF has important duties and roles to overcome child trafficking in Vietnam.To overcome this child trafficking in Vietnam, UNICEF has more roles in education aspects. It’s because with education which is implemented well for next generation in Vietnam, so hopefully Vietnam will have competence human resource and it’s also will reduce poverty there.Keywords: UNICEF, MDG’s, Child Trafficking, Vietnam, Pluralis